VISUALIZATION OF ONTOLOGY-BASED DATA WAREHOUSE FOR MALARIA SPREAD INCIDENCES USING PROTEGE - Aan Kardiana; Nova Eka Diana (Faculty of Computer Science Universitas Indonesia, 2016)
Malaria is a communicable disease caused by a plasmodium parasite and transmitted among human byAnopheles mosquitoes. Late medication of this disease can cause a death of patients. Indonesia hasmany endemic areas with a high volume of patients diagnosed by Malaria. Currently, this incidencesdata are stored in Microsoft Excel files. We need to build a data warehouse to easily manage thesedata. Here, we create ontology of Malaria’s incidence data to figure out the important information inMalaria data warehouse that we want to build. We identify entities, classes, subclasses, andrelationships between these entities. We employed Protégé to build and visualize the ontology ofMalaria’ incidence data.